Police And Public Image Satisfaction On Quality Of Service In Corner Driver's License Unit (Economic and Bussiness Faculty, Dr Soetomo University, 2017)
This research discusses, the influence of physical environmental, technical and functional quality toward customer satisfaction and Police institution image (study at SIM Corner in Indonesia). This purposed of this research to evaluate and analyze. The population of this research is the customer’s as the applicant extension of SIM A and SIM C and also SIM A and SIM C at the service management of SIM Corner in Indonesia, as respondent being analyzed are 150 customer’s at SIM Corner in Surabaya city and Sidoarjo district, and using non-probability sampling, besides it also using accidental sampling. Date tool using the Structural Equation Modelling (SEM) with path analysis, and the result of this research show that: physical environmental quality proven that it improve the customer satisfaction at SIM Corner; technical quality proven that it improve the customer satisfaction at SIM Corner; functional quality proven that it improve the customer satisfaction at SIM Corner; physical environmental quality proven that it improve the Police institution image; technical quality proven that it improve the Police institution image; functional quality proven that it improve the Police institution image; consumer satisfaction proven that it improve the Police institution image in Indonesia.